FEB Campaign to International Travelers For Social and Culture Tourism Village in Banten - Kambara, Roni; Pratiwi, Refi; Supriadi , Adih; Arisondha, Edy (MOVE: Journal of Community Service and Engagement, 2025)
This activity was held to introduce Banten Culture and Tourism to foreign tourists visiting Toraja. Introducing Banten tourism to tourists, especially foreign tourists, has strategic goals in various aspects. Banten, which has a wealth of culture, history, and nature, can be an interesting destination if introduced properly.  In addition, this activity is also in order to build networks and increase exposure of tourist destinations globally.In accordance with these objectives, this activity has been carried out smoothly. Factors causing the success and smoothness of this activity include support and cooperation from various parties (stakeholders). The mission of promoting/introducing Culture and Tourism in Banten to foreign tourists was carried out well, namely being conveyed to them, the foreign tourists. It is hoped that with this activity, foreign tourists can also come to Banten, enjoy the beauty of Banten tourism, so that Banten can be more widely known.